An energetic device base structure and preparation method thereof
By forming micro-nano pores on the inner surface of the filling holes of the energy-containing device base and filling strong oxidant crystals, the problem of voids in the prior art when filling energy-containing materials is solved, which significantly improves the detonation response time of the device and reduces power consumption.
Patent Information
- Application Number
- CN202510012262.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The smooth structure of the inner surface of the filling hole of the existing energy-containing device base leads to a gap when the energy-containing material is filled, resulting in the inability to quickly and effectively add heat to the energy-containing material after electric heat excitation, and the detonation response time is too long.
A plurality of micro-nano pores are formed on the inner surface of the filled holes, and strong oxidant crystals are filled in these micro-nano pores to form a micro-nano pore energy-containing boundary structure to increase the specific surface area and friction coefficient of the filled holes.
By rapidly and efficiently heating the energy-containing boundary structure of micro-nano pores, it quickly detonates and releases a large amount of energy, and then detonates the energy-containing material in the fill hole, significantly improving the detonation response time of the entire device and reducing power consumption.
Smart Images

Figure CN119480800B_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present disclosure belong to the technical field of energetic devices, and specifically relate to an energetic device base structure and a preparation method thereof. Background Art
[0002] At present, energetic devices (chips) are the key direction of cutting-edge research. After being integrated with core chips, energetic devices can play the role of physically destroying key core chips in specific scenarios, which is an important means to prevent technology leakage.
[0003] like Figure 1 As shown, an existing energetic base and energetic device structure is composed of an energetic base 10, an energetic material filling hole 20 and an energetic material 30. Figure 2 As shown, due to process limitations, the energetic material 30 is prone to form filling defects 40 at the contact surface of the filling hole 20. After thorough research, it was found that it is precisely because the inner surface of the existing filling hole 20 is a smooth structure that the energetic material cannot be in close contact with the surface of the filling hole 20 in some parts during the filling and solvent volatilization and drying process, and there are gaps, so that after electrothermal excitation, heat cannot be quickly and effectively added to the energetic material, so the detonation response time is too long.
[0004] In view of the above problems, it is necessary to propose an energetic device base structure and a preparation method thereof that are reasonably designed and can effectively solve the above problems. Summary of the invention
[0005] The embodiments of the present disclosure aim to solve at least one of the technical problems existing in the prior art and provide an energetic device base structure and a method for preparing the same.
[0006] One aspect of the embodiments of the present disclosure provides an energetic device base structure, including a base, a micro-nano pore energetic boundary structure, and an energetic material filling body;
[0007] The base is provided with a plurality of filling holes;
[0008] The micro-nano pore energetic boundary structure is arranged on the inner surface of the filling hole;
[0009] The energetic material filling body is filled in the filling hole; wherein,
[0010] The micro-nano pore energetic boundary structure comprises a plurality of micro-nano pores and strong oxidant crystals filled in the micro-nano pores.
[0011] Optionally, the micro-nano pores are arranged on the inner surface of the filling hole, wherein the pore size of the micro-nano pores is irregular, and the pore size range of the micro-nano pores is 0.3 μm~3 μm.
[0012] Optionally, the depth of the filling hole ranges from 100 μm to 300 μm, and the diameter of the filling hole ranges from 100 μm to 500 μm.
[0013] Optionally, the strong oxidant crystals are sodium perchlorate crystals.
[0014] Optionally, the base is a single crystal silicon wafer or a silicon wafer with an oxide layer on the surface.
[0015] Another aspect of the present disclosure provides a method for preparing an energetic device base structure, the method comprising:
[0016] providing a base, and patterning the base to form a plurality of filling holes on the base;
[0017] Patterning the inner surface of the filling hole to form a plurality of micro-nano pores on the inner surface of the filling hole;
[0018] Filling the micro-nano pores with strong oxidant crystals to form a micro-nano pore energetic boundary structure;
[0019] An energetic material filling body is filled in the filling hole to form the energetic device base structure.
[0020] Optionally, patterning the base to form a plurality of filling holes on the base includes:
[0021] Cleaning the base;
[0022] forming a photoresist layer on the cleaned base, and sequentially exposing and developing the photoresist layer to form an opening on the photoresist layer;
[0023] The base is subjected to TMAH vapor phase etching along the opening to form a plurality of the filling holes on the base.
[0024] Optionally, patterning the inner surface of the filling hole to form a plurality of micro-nano pores on the inner surface of the filling hole includes:
[0025] Placing the base formed with the plurality of filling holes in a corrosion solution containing HF, HNO3 and distilled water for chemical corrosion, wherein the entire chemical corrosion process is carried out in a constant temperature water bath at 28°C to 30°C;
[0026] Prepare a 10% to 15% NaNO2 aqueous solution and drip it into the etching solution at a constant rate of 330umL / min to 350umL / min;
[0027] The etching solution is continuously stirred at a stirring rate of 180 r / min to 200 r / min to form a plurality of micro-nano pores on the inner surface of the filling hole by etching;
[0028] Among them, during the entire corrosion process, the mass fraction of HF always remains at 14%~16%, the mass fraction of HNO3 always remains at 4%~5.5%, and the corrosion time is 1h~1.5h.
[0029] Optionally, the filling of the micro-nano pores with strong oxidant crystals comprises:
[0030] Cleaning and drying the base having the plurality of micro-nano pores formed thereon;
[0031] Vacuuming the base to remove air bubbles in the filling hole;
[0032] The base is placed in a saturated sodium perchlorate ethanol solution for complete immersion;
[0033] The soaked base is ultrasonically cleaned and placed in an oven for low-temperature drying to remove the ethanol solvent, so that the sodium perchlorate is recrystallized in the micro-nano pores to form sodium perchlorate crystals.
[0034] Optionally, filling the filling hole with an energetic material filling body comprises:
[0035] The energetic material filling body is filled into the filling hole by immersion filling or by combining ultrasonic process, or by screen printing process.
[0036] The energetic device base structure and preparation method of the disclosed embodiment include a base, a micro-nano pore energetic boundary structure and an energetic material filling body; the base is provided with a plurality of filling holes; the micro-nano pore energetic boundary structure is provided on the inner surface of the filling hole; the energetic material filling body is filled in the filling hole; wherein the micro-nano pore energetic boundary structure includes a plurality of micro-nano pores and strong oxidant crystals filled in the micro-nano pores. By providing the micro-nano pore energetic boundary structure on the surface of the filling hole, the specific surface area and friction coefficient of the filling hole are greatly increased, and the strong oxidant crystals are tightly filled in the micro-nano pores of the micro-nano scale. After thermal excitation, heat energy is first quickly and effectively added to the micro-nano pore energetic boundary structure, which is quickly detonated to release a large amount of energy, and then the energetic material in the filling hole is detonated, which significantly improves the detonation response time of the entire device and reduces power consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a structural schematic diagram of an energetic device base structure in the prior art;
[0038] Figure 2 for Figure 1 A partial enlarged view of position A in the middle;
[0039] Figure 3 This is a structural schematic diagram of an energetic device base structure according to one embodiment of the present disclosure;
[0040] Figure 4 for Figure 3 A partial enlarged view of position B in the middle;
[0041] Figure 5 It is a schematic flow chart of a method for preparing an energetic device base structure according to another embodiment of the present disclosure;
[0042] Figures 6 to 10 This is a preparation process flow chart of a method for preparing an energetic device base structure according to another embodiment of the present disclosure. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand the technical solutions of the embodiments of the present disclosure, the embodiments of the present disclosure are further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0044] like Figure 3 and Figure 4 As shown, one aspect of an embodiment of the present disclosure provides an energetic device base structure 100 , including a base 110 , a micro-nano pore energetic boundary structure 120 , and an energetic material filling body 130 .
[0045] The base 110 is provided with a plurality of filling holes 111. Specifically, a surface of one side of the base 110 is provided with a plurality of filling holes 111.
[0046] The micro-nano pore energetic boundary structure 120 is disposed on the inner surface of the filling hole 111 .
[0047] The energetic material filler 130 is filled in the filling hole 111. In this embodiment, the particle size of the energetic material filler is in the range of 20 μm to 50 μm, which can achieve a better filling effect.
[0048] It should be noted that, in this embodiment, the energetic material filling body 130 can be made of corresponding energetic materials according to actual needs.
[0049] Among them, Figure 4 As shown, the micro-nano pore energetic boundary structure 120 includes a plurality of micro-nano pores 121 and strong oxidant crystals 122 filled in the micro-nano pores 121. The strong oxidant crystals 122 are filled in the micro-nano pores 121 of micro-nano scale and are tightly combined.
[0050] The energetic device base structure of the disclosed embodiment greatly increases the specific surface area and friction coefficient of the filling hole by setting a micro-nano pore energetic boundary structure on the surface of the filling hole, and the strong oxidant crystals are tightly filled in the micro-nano pores of the micro-nano scale. After thermal excitation, heat energy can first be quickly and effectively added to the micro-nano pore energetic boundary structure, which quickly detonates and releases a large amount of energy, thereby detonating the energetic material in the filling hole, thereby significantly improving the detonation response time of the entire device and reducing power consumption.
[0051] For example, Figure 4 As shown, the micro-nano pores 121 are arranged on the inner surface of the filling hole 111, wherein the pore size of the micro-nano pores 121 is irregular, and the pore size of the micro-nano pores 121 ranges from 0.3 μm to 3 μm, which belongs to the pore structure of micro-nano order.
[0052] Compared with the smooth inner surface structure of the filling hole of the existing energetic device base, the nanoscale micro-nano pore 121 structure of the embodiment of the present disclosure greatly increases the specific surface area and friction coefficient of the filling hole 111, providing good conditions for the crystallization of strong oxidants.
[0053] Exemplarily, in this embodiment, the hole depth of the filling hole 111 ranges from 100 μm to 300 μm, and the hole diameter of the filling hole 111 ranges from 100 um to 500 um.
[0054] There is no specific limitation on the shape of the filling hole 111 . The filling hole 111 may be a round hole, a square hole, a slit-shaped structure or other structures, and its main function may be regarded as a carrier of energetic materials.
[0055] It should be noted that the filling holes 111 may be evenly distributed on the surface of one side of the base 110 , or may be regionally distributed, and the selection may be made according to actual needs.
[0056] For example, in this embodiment, the strong oxidant crystals 122 may be sodium perchlorate crystals. Of course, the strong oxidant crystals 122 may also be other types of crystals, as long as they have strong oxidizing properties. This embodiment does not specifically limit the type of the strong oxidant crystals 122, and may be selected according to actual needs.
[0057] For example, in this embodiment, the base 110 can be a single crystal silicon wafer or a silicon wafer with an oxide layer on the surface. Specifically, the base 110 can be a current mainstream 4-inch to 12-inch single crystal silicon wafer with a thickness of 300 μm to 500 μm or a silicon wafer with an oxide layer structure on the surface.
[0058] It should be noted that the present embodiment does not impose any specific limitation on the material of the base 110 , and the material can be selected according to actual needs.
[0059] The energetic device base structure of the disclosed embodiment can be applied to chips, various (micro) devices or structures integrating energetic materials, etc.
[0060] like Figure 5 As shown, another aspect of the embodiment of the present disclosure provides a method S100 for preparing an energetic device base structure, the preparation method S100 comprising:
[0061] S110, providing a base, and patterning the base to form a plurality of filling holes on the base.
[0062] Specifically, Figure 6 As shown, a base 110 is provided, and a patterning is performed on one side of the base 110 by an etching process to form a plurality of filling holes 111 on the base. The base 110 may be a single crystal silicon wafer or a silicon wafer with an oxide layer on the surface. In other words, the base 110 may be a silicon wafer. Specifically, the base 110 may be a currently mainstream 4-inch to 12-inch single crystal silicon wafer with a thickness of 300 μm to 500 μm or a silicon wafer with an oxide layer structure on the surface.
[0063] In this embodiment, according to the structural design and the requirements of verticality and uniformity, a TMAH vapor phase etching process is used to prepare a filling hole on the base. The specific steps may be as follows:
[0064] 1) Cleaning the base.
[0065] Specifically, the base 110 is cleaned using an industrial standard wet cleaning process.
[0066] 2) forming a photoresist layer on the cleaned base, and sequentially exposing and developing the photoresist layer to form an opening on the photoresist layer.
[0067] Specifically, a photoresist layer is coated on one side surface of the cleaned base 110 , and the photoresist layer is sequentially exposed and developed to transfer the pattern of the filling hole 111 to the photoresist layer to form a corresponding opening on the photoresist layer.
[0068] 3) Performing TMAH vapor phase etching on the base along the opening to form a plurality of filling holes on the base. After the etching is completed, the residual photoresist layer is removed.
[0069] Among them, TMAH vapor etching mainly includes the following steps:
[0070] First, the substrate 110 with a patterned mask is placed in a wafer fixture with the surface to be etched facing downward.
[0071] Next, build the vapor etching equipment, turn on the pressure sensor, temperature sensor, heater, rotating motor, and cooling water pump, and start timing.
[0072] Again, according to the hole depth design requirements, the etching equipment is turned off after stable etching along the opening for a certain period of time.
[0073] Finally, after the structure on one side is prepared, the above process is repeated to prepare the structure on the other side, so as to form a structure on one side of the base 110 as shown in FIG. Figure 6 A plurality of filled holes 111 are shown, and the base 110 is removed and tested using a confocal microscope.
[0074] It should be noted that, in this embodiment, the base can adopt the currently mainstream 4-inch to 12-inch single crystal silicon wafer with a thickness of 300 μm to 500 μm or a silicon wafer with an oxide layer structure on the surface.
[0075] It should be further explained that the process of patterning the base to form the filling hole may also use other etching processes, which are not specifically limited in this embodiment and can be selected according to actual needs.
[0076] S120, patterning the inner surface of the filling hole to form a plurality of micro-nano pores on the inner surface of the filling hole.
[0077] Specifically, in the embodiment, a chemical etching process is used to image the surface of the filling hole 111, and the surface of the filling hole 111 is imaged by using F in an acidic environment. - The inner surface of the filling hole 111 is chemically etched to form a Si complex. Figure 7 The multiple micro-nano pores 121 shown. Among them, Figure 8 For the general Figure 7 Schematic diagram of the structure of the micro-nano pore 121 after local magnification of position C in FIG.
[0078] The process of chemically etching the filling hole 111 may be as follows:
[0079] 1) Placing the base formed with the plurality of filling holes in a corrosion solution containing HF, HNO3 and distilled water for chemical corrosion, wherein the entire chemical corrosion process is carried out in a constant temperature water bath at 28°C to 30°C.
[0080] Specifically, in this embodiment, preferably, the base 110 formed with a plurality of filling holes 111 is put into a polytetrafluoroethylene beaker filled with a mixture of HF, HNO3 and distilled water, wherein the entire chemical etching process is carried out in a constant temperature water bath at 28°C.
[0081] 2) Prepare a 10% to 15% NaNO2 aqueous solution and drip it into the etching solution at a constant rate of 330umL / min to 350umL / min.
[0082] Specifically, in this embodiment, preferably, a 10% NaNO2 aqueous solution is prepared and dripped into a polytetrafluoroethylene beaker at a constant rate of 330umL / min. The gas generated during the corrosion process will adhere to the surface of the filling hole 111, affecting the corrosion process. The dripping of the NaNO2 aqueous solution can make the solution produce bubbles and burst the gas attached to the surface, playing a similar role as stirring.
[0083] 3) continuously stirring the etching solution at a stirring rate of 180 r / min to 200 r / min to form a plurality of micro-nano pores on the inner surface of the filling hole.
[0084] Among them, during the entire corrosion process, the mass fraction of HF always remains at 14%~16%, the mass fraction of HNO3 always remains at 4%~5.5%, and the corrosion time is 1h~1.5h.
[0085] Specifically, in this embodiment, preferably, a polytetrafluoroethylene stirring rod is used for continuous stirring at a rate of 180 r / min to ensure that the etching liquid continuously acts on the inner surface of the filling hole 111 under the action of mechanical stirring. In the entire etching process, the mass fraction of HF is always maintained at 15.6%, the mass fraction of HNO3 is always maintained at 5.2%, and the etching time is 1 hour.
[0086] After the etching is completed, the acid solution on the surface of the base 110 is cleaned with distilled water, and the base is placed in a drying oven at 60° C. for 24 hours to evaporate the surface moisture, and a coating is formed on the inner surface of the filling hole 111. Figure 8 Multiple micro-nano pores 121 are shown.
[0087] It should be noted that the pore size of the micro-nano pores 121 formed by the chemical etching process is irregular, and the pore size of the micro-nano pores 121 ranges from 0.3 μm to 3 μm.
[0088] S130, filling the micro-nano pores with strong oxidant crystals to form a micro-nano pore energetic boundary structure.
[0089] Specifically, Fig. 9 As shown, in this embodiment, ultrasonic immersion can be used to fill the micro-nano pores 121 with strong oxidant crystals 122 to form the micro-nano pore energetic boundary structure 120 .
[0090] The process of filling the micro-nano pores 121 with strong oxidant crystals by ultrasonic immersion can be as follows:
[0091] 1) Cleaning and drying the substrate on which the plurality of micro-nano pores are formed.
[0092] Specifically, the base 110 having the plurality of micro-nano pores 121 formed therein in step S120 is cleaned and then dried in a drying oven at 60° C. to ensure that the surface is clean.
[0093] 2) Vacuuming the base to remove air bubbles in the filling hole.
[0094] Specifically, the polytetrafluoroethylene beaker container and the cleaned and dried base 110 are placed in a vacuum chamber and evacuated to remove bubbles inside and on the surface of the filling hole 111.
[0095] 3) The base is placed in a saturated sodium perchlorate ethanol solution for complete immersion.
[0096] Specifically, the base 110 is placed horizontally in a polytetrafluoroethylene beaker container to ensure that the saturated sodium perchlorate ethanol solution can completely immerse the base 110 .
[0097] 4) The base after immersion is ultrasonically cleaned and placed in an oven for low-temperature drying to remove the ethanol solvent, so that the sodium perchlorate is recrystallized in the micro-nano pores to form sodium perchlorate crystals.
[0098] Specifically, place the polytetrafluoroethylene beaker into the working tank of the ultrasonic cleaner to ensure that the ultrasonic wave can act evenly on the solution and the base 110. Start the ultrasonic cleaner, set the ultrasonic frequency to 40Hz, the power to 80W, and the ultrasonic treatment time to 30 minutes; after the ultrasonic treatment, take the base 110 out of the solution and dry it in an oven at low temperature (60°C) to remove the ethanol solvent and ensure that the sodium perchlorate is recrystallized in the micro-nano pores 121 to form sodium perchlorate crystals. In other words, the micro-nano pores 121 are formed as follows Fig. 9 The strong oxidant crystals 122 shown in FIG. Fig.10 The micro-nano porous energetic boundary structure 120 is shown.
[0099] S140, filling an energetic material filling body into the filling hole to form the energetic device base structure.
[0100] Specifically, in this embodiment, immersion filling can be used, or ultrasonic technology can be combined with screen printing and other process methods, such as Fig.10As shown, an energetic material filler 130 is filled into the filling hole 111 to form the energetic device base structure 100. In this embodiment, the particle size of the energetic material filler 130 is 20 μm to 50 μm, the pore size of the filling hole 111 is 100 μm to 500 μm, the pore depth of the filling hole 111 is 100 μm to 300 μm, and the ultrasonic immersion filling time is 30 min to 60 min, which can achieve a better filling effect.
[0101] The preparation method of the energetic device base structure of the embodiment of the present disclosure includes: providing a base, patterning the base to form a plurality of filling holes on the base; patterning the surface of the filling holes to form a plurality of micro-nano pores on the inner surface of the filling holes; filling the micro-nano pores with strong oxidant crystals to form a micro-nano pore energetic boundary structure; filling the filling holes with energetic material filling bodies to form an energetic device base structure. By forming the micro-nano pore energetic boundary structure on the surface of the filling holes, the specific surface area and friction coefficient of the filling holes are greatly increased, and the strong oxidant crystals are tightly filled in the micro-nano pores of the micro-nano scale. After thermal excitation, heat can first be quickly and effectively added to the micro-nano pore energetic boundary structure, which is quickly detonated to release a large amount of energy, and then the energetic material in the filling holes is detonated, which significantly improves the detonation response time of the entire device and reduces power consumption.
[0102] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the embodiments of the present disclosure, but the embodiments of the present disclosure are not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the embodiments of the present disclosure, and these modifications and improvements are also considered to be within the protection scope of the embodiments of the present disclosure.
Claims
1. An energetic device base structure, characterized in that: It includes a base, a micro-nano pore energetic boundary structure and an energetic material filling body; The base is provided with a plurality of filling holes; The micro-nano pore energetic boundary structure is arranged on the inner surface of the filling hole to increase the specific surface area and friction coefficient of the filling hole; The energetic material filling body is filled in the filling hole; wherein, The micro-nano pore energetic boundary structure comprises a plurality of micro-nano pores arranged on the inner surface of the filling hole and strong oxidant crystals filled in the micro-nano pores.
2. The energetic device base structure according to claim 1, characterized in that: in, The pore size of the micro-nano pores is irregular, and the pore size range of the micro-nano pores is 0.3 μm to 3 μm.
3. The energetic device base structure according to claim 1, characterized in that: The depth of the filling hole ranges from 100 μm to 300 μm, and the diameter of the filling hole ranges from 100 μm to 500 μm.
4. The energetic device base structure according to any one of claims 1 to 3, characterized in that: The strong oxidant crystals are sodium perchlorate crystals.
5. The energetic device base structure according to any one of claims 1 to 3, characterized in that: The base is a single crystal silicon wafer or a silicon wafer with an oxide layer on the surface.
6. A method for preparing an energetic device base structure, characterized in that: The method comprises: providing a base, and patterning the base to form a plurality of filling holes on the base; Patterning the inner surface of the filling hole to form a plurality of micro-nano pores on the inner surface of the filling hole; Filling the micro-nano pores with strong oxidant crystals to form an energetic boundary structure of the micro-nano pores, wherein the energetic boundary structure of the micro-nano pores is used to increase the specific surface area and friction coefficient of the filled pores; An energetic material filling body is filled in the filling hole to form the energetic device base structure.
7. The method according to claim 6, characterized in that The step of patterning the base to form a plurality of filling holes on the base includes: Cleaning the base; forming a photoresist layer on the cleaned base, and sequentially exposing and developing the photoresist layer to form an opening on the photoresist layer; The base is subjected to TMAH vapor phase etching along the opening to form a plurality of the filling holes on the base.
8. The method according to claim 6, characterized in that The patterning of the inner surface of the filling hole to form a plurality of micro-nano pores on the inner surface of the filling hole includes: Placing the base formed with the plurality of filling holes in a corrosion solution containing HF, HNO3 and distilled water for chemical corrosion, wherein the entire chemical corrosion process is carried out in a constant temperature water bath at 28°C to 30°C; Prepare a 10% to 15% NaNO2 aqueous solution and drip it into the etching solution at a constant rate of 330umL / min to 350umL / min; The etching liquid is continuously stirred at a stirring rate of 180 r / min to 200 r / min to form a plurality of micro-nano pores on the inner surface of the filling hole by etching; wherein, During the entire corrosion process, the mass fraction of HF always remained at 14%~16%, the mass fraction of HNO3 always remained at 4%~5.5%, and the corrosion time was 1h~1.5h.
9. The method according to claim 6, characterized in that The method of filling the micro-nano pores with strong oxidant crystals comprises: Cleaning and drying the base having the plurality of micro-nano pores formed thereon; Vacuuming the base to remove air bubbles in the filling hole; The base is placed in a saturated sodium perchlorate ethanol solution for complete immersion; The soaked base is ultrasonically cleaned and placed in an oven for low-temperature drying to remove the ethanol solvent, so that the sodium perchlorate is recrystallized in the micro-nano pores to form sodium perchlorate crystals.
10. The method according to claim 6, characterized in that The step of filling the filling hole with an energetic material filling body comprises: The energetic material filling body is filled into the filling hole by immersion filling or by combining ultrasonic process, or by screen printing process.
Citation Information
Patent Citations
Porous silicon-based explosive
US20040244889A1
Chip and manufacturing method therefor
WO2020146994A1